DAKWAH SOSIAL DAN FILANTROPI ISLAM: TRANSFORMASI, KESEJAHTERAAN DAN KEADILAN BAGI MASYARAKAT - Surizkika, Aldi (Fakultas Ilmu Dakwah dan Komunikasi, 2024)
This research examines the importance of social da'wah and philanthropy in economic development, welfare and social justice in Muslim societies. Social da'wah focuses on socio-economic development, socio-culture, education, environmental issues, and infrastructure development that affect daily life. Islamic philanthropy is used as one of the implementations of social da'wah to achieve social justice goals. Previous research shows that Islamic philanthropy has the potential to support social justice, and comprehensive social da'wah can bring about real change in society. Therefore, this study aims to explore social da'wah activities and philanthropy as an effort in building the economy, realizing welfare, and creating social justice. Through a conceptual approach and literature review, this research outlines the concept of social da'wah in Islam and the importance of effective management through social approaches. In addition, this research also discusses the role of philanthropy in Islam as a form of charity that includes physical gifts, intangible gifts, and spiritual gifts to improve the welfare of others. The results of this research are expected to provide a better understanding of the importance of social da'wah and the role of philanthropy in Islam in bringing about positive changes in society. By integrating social da'wah and philanthropy, it is hoped that sustainable economic development, equitable welfare, and better social justice can be realized in Muslim societies.